Science Learning Performance and Retention of Biology Concepts Among Secondary Students - Adebisi, Rufus Olanrewaju; Adeyemi, Motunrayo I; Umbugadu, Mary Ashelo (Universitas Sembilanbelas November Kolaka, 2021)
This study investigated into effects of science learning materials on performance and retention of biology concepts among senior secondary school two students in Afijio local government area of Oyo State. The study was Quasi-experimental involving pretest, posttest equivalent group design. In this design, 40 students were randomly selected from SS2, pretested to ascertain their group equivalence, and then divided into two groups (experimental and control) using the lottery method of sampling techniques. The experimental group was taught biology concepts with science learning materials,while the control group was taught the same concepts without science learning materialsfor three weeks. The two groups were pretested and post-tested for performance and retention, respectively. The data collected were analyzed using a simple percentage method, mean, and standard deviation. Based on the data generated and results obtained from the experiment, the findings revealed that the use of science learning materialsin the leaching of Biology concepts significantly improves the academic performances, enhances the retention ability of students involved in the study. The study also revealed that students exposed to the use of science learning materialsin the teaching of biology concepts generally had better academic performances and retention ability than students who were not exposed to the use of science learning materialsin the experiment. The study recommended, among others, that the Ministry of Education should provide science learning materials for effective teaching and learning of Biology concepts in Oyo State Senior Secondary Schools.Â Keywoard: Science Learning Performance,Â Retention,Â Biology Concepts